Mongubingo Dalam Perspektif Budaya Masyarakat Adat Gorontalo - Ramli Mahmud; Asmun Wantu; Yayan Sahi (Universitas Negeri Manado, 2022)
Mungubingois the embodiment of a variety of cultural heritages that are still preserved by the indigenous people of Gorontalo to this day whose customs are based on syarah and syarah based on Qitabullah (ASQ). Mongubingo is the value of wisdom of the indigenous people of Gorontalo. In a formal juridical perspective, mongubingo does not find a rational place to be practiced. The claim of WHO and Komnas Perempuan against the implementation of the tradition of female circumcision as a violation of human rights is actually considered a very obligatory thing, especially for women in Gorontalo. Based on this debate, this study aims to examine how the Mongubingo Perspective in Gorontalo Indigenous Culture and the practice of the Mongubingo tradition in its formal juridical perspective. In order to achieve this goal, the qualitative method with an ethnogarphy approach is considered representative in mapping the research objectives. The results showed that, for the indigenous people of Gorontalo, mongubingo is an obligation for women to carry out a process of self-purification as a form of harmony between custom and religion. In addition, from a formal juridical perspective, mongubingo does not receive formal recognition, but on the other hand, there is a perspective that must be obeyed and realized by both the state and citizens who are recognized and respected for the basic right to belief in religion and recognition of customary law communities. Based on these findings, the formulation of state policies and regulations should accommodate all customary entities so that there is no conflict between the state and indigenous peoples.